THE WORLD TRADE ORGANIZATION AND UZBEKISTAN - Khayrullaeva, Mukhlisakhon Nuriddin qizi (Educational Research in Universal Sciences, 2022)
The World Trade Organization(WTO) is the only international organization that regulates international trade. This makes it the only organization, which has the potential to give Uzbekistan access to bigger markets and opportunities, thus boosting its economy as a whole. However, although Uzbekistan applied for membership in the WTO almost 30 years ago, it has not been approved as of the end of 2022. As currently Uzbekistan’s accession into the World Trade Organization is an ongoing and highly debated topic, this paper aims to go through the reasons why Uzbekistan has not been accepted yet as well as advantageous and negative aspects of accession and finally drawing a conclusion of the benefits of the membership will overcome the latent drawbacks.